Superior properties of CellTrace Yellow™ as a division tracking dye for human and murine lymphocytes - Tempany, Jessica C (Immunol Cell Biol, 2017)
The discovery of cell division tracking properties of 5‐(and‐6)‐carboxyfluorescein diacetate succinimidyl ester (CFSE) by Lyons and Parish in 1994 led to a broad range of new methods and numerous important biological discoveries. After labeling, CFSE is attached to free amine groups and intracellular proteins in the cytoplasm and nucleus of a cell, and halves in fluorescence intensity with each round of cell division, enabling enumeration of the number of divisions a cell has undergone. A range of popular division tracking dyes were subsequently developed, including CellTrace Violet (CTV), making available the green fluorescent channel previously occupied by CFSE. More recently, CellTrace Yellow (CTY) and CellTrace Far Red (CTFR), each with unique fluorescence properties, were introduced. In a comparison, we found that the fluorescence values of both dyes were well separated from autofluorescence, and enabled a greater number of divisions to be identified than CTV, before this limit was reached. These new dyes provided clear and well‐separated peaks for both murine and human B lymphocytes, and should find wide application. The range of excitation/emission spectra available for division tracking dyes now also facilitates multiplexing, that is, the labeling of cells with different combinations of dyes to give a unique fluorescence signature, allowing single cell in vitro and in vivo tracking. The combinatorial possibilities are significantly increased with these additional dyes.